Automatic Connection of Virtual Circuits in Smart Substations Based on Chaotic Two-Dimensional Mapping Sine and Cosine Algorithm - Guofeng JIN; Shifeng YANG; Lingling LIU; Kai WANG; Qiang WANG; Lei WANG (Zhongguo dianli)
In this paper, a virtual loop automatic connection technology based on two-dimensional chaotic sine-cosine algorithm is proposed. Firstly, a virtual terminal matching model involving distance weight vector is constructed by using Jaro-Winkler distance. Then, on the basis of the historical data of virtual connection, the optimal distance weight vector is solved by using the two-dimensional chaotic sine-cosine algorithm. Finally, a 66 kV substation in eastern Mongolia is taken as an example to match virtual terminals with the proposed method. The results show that the virtual terminal connection results obtained by the proposed method are more accurate and more efficient than those obtained by the prior art.